Incidence of Gastrointestinal Parasites in Zebu and N’dama Breeds from Cattle Ranches in Jos Plateau, Nigeria - Dogo G. Abraham; Arinze S. Chukwuemeka; Oshadu David Omagbe (Journal of Parasite Research, 2020)
The incidence of gastrointestinal parasites in Zebu and N’dama breeds known to be trypanotolerant cattle from some ranches in Jos Plateau was investigated at the peak of the raining season, August to October, 2018. A total of 150 cattle from some Ranches in Jos Plateau were randomly selected for faecal sampling out of which 85 were Zebu (Bos indicus) and 65 were N’dama (Bos taurus) breeds respectively. The samples were analyzed for ova of gastrointestinal parasites using the simple flotation and sedimentation techniques and the results were interesting. The strongyloids, Oesophagostomumradiatum had the highest incidence of 4.7% followed by the Trichostrongylus species with 4%. Fasciolagigantica and Haemonchusplacei both were 3.3%. Then Paramphistomumcervi 2%; bovine hook worm, Bunostomumphlebotomum 1.3%, Taenia saginata1.3%, Schistosoma bovis 1.3% and Nematodirusspathiger 0.7%. The incidence of nematodes, cestodes and trematodes in this study in the raining season was significant (p<0.05) and could pose production and economic threat to institutional farms and ranches in the development of livestock and dairy industries in Nigeria. There should be a strong policy on the control of gastrointestinal parasites in the country for farmers to benefit from their contribution in ensuring food security.
Keywords: Incidence